2007
DOI: 10.1063/1.2732496
|View full text |Cite
|
Sign up to set email alerts
|

On the theory of frequency-quadrupling gyroklystrons

Abstract: In this paper, frequency-quadrupling three-cavity gyroklystrons with successive frequency-doubling in each stage are considered. First, it is shown that such device operating in the W band at the TE 4,2 -mode can deliver up to 30 kW output power in the regime of stable amplification with the density of Ohmic losses acceptable for continuous-wave ͑cw͒ operation. The corresponding efficiency is in the range of 17%-20%. Then, the device is scaled to 0.5 THz frequency and optimized for operation at the TE 4,5 -mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…This fact was taken into account in a number of papers devoted to the analysis of gyrotron efficiency at short wavelengths ͑see, e.g., Refs. 7,8,18,and 19͒. To take this effect into account, the electronic efficiency defined for the case of devices with energy recuperation above by Eqs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact was taken into account in a number of papers devoted to the analysis of gyrotron efficiency at short wavelengths ͑see, e.g., Refs. 7,8,18,and 19͒. To take this effect into account, the electronic efficiency defined for the case of devices with energy recuperation above by Eqs.…”
Section: Discussionmentioning
confidence: 99%
“…It can, however, be rather high 7 in three-cavity, frequency-quadrupling gyrotrons where the first cavity operates at the fundamental, second cavity-at the second and the last cavity-at the fourth harmonic ͑a so-called 1-2-4 circuit; here, numbers 1, 2, and 4 correspond to harmonic numbers resonant in each cavity͒. In recent papers, 8,9 this concept originally proposed by Guo 10 was elaborated in more detail. The present study, in addition to analyzing conventional gyrodevices with and without electron prebunching, also includes the analysis of benefits from using depressed collectors in such frequencyquadrupling schemes.…”
Section: Introductionmentioning
confidence: 96%
“…It should be noticed that the similar propagation properties of the two modes are essential to the optimal performance of the designed DQMC. As seen from the mode selection criteria and the operation principle of the gyro-multiplier [4], [5], the k 0 , k z , k ⊥ , m, μ m, n , and ω of the T E 4, 9 mode are (nearly or exactly) four times in value of their counterparts in T E 1, 3 mode. This…”
Section: Dual-frequency Quasi-optical Mode Convertermentioning
confidence: 99%
“…A GYRO-MULTIPLIER is a high-power THz signal generator based on the combination of traditional gyrotron-like beam-wave interaction [1] and frequency multiplication [2]. Although the operation of the gyro-multiplier has been studied extensively in theory [3], [4] and demonstrated successfully in experiments [5], [6] in recent years, the study of a proper output system for such device has not been reported in the literature. Unlike the traditional gyrotrons of single-mode operation, the output of a gyro-multiplier contains two modes with one operating at the fundamental electron cyclotron resonance and the other being excited at one of the high-order harmonics.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce the strength of working magnetic field, the gyrotron needs to operate at cyclotron harmonics (when the gyrotron working at nth cyclotron harmonic, the corresponding working magnetic field can be reduced to 1/n). In order to operate at higher harmonics for small-orbit gyrotron, three-cavity fourth harmonic gyroklystron with successive frequency-doubling in each cavity was proposed [1][2]. The schematic of frequency-quadrupling gyroklystron is shown in Fig.1.…”
Section: Introductionmentioning
confidence: 99%